Insurance and liquidity : panel evidence - Shankar, Rashmi (Policy research working paper, 2005)
"The author presents evidence that balance sheet effects are critical determinants of both the likelihood of a crisis and of income losses following a crisis. She tests the validity of "insurance" and "liquidity" models of currency crisis. Both models predict that the occurrence of a balance of payments crisis is conditional on the health of the nation's accounts in relation to the rest of the world. Problems in the balance sheet either cause a financial crisis that develops into a run on the central bank, or generate a run on the central bank once contingent liabilities exceed reserves and the yield differential moves against domestic assets. Estimations of crisis likelihoods based on several specifications of single and simultaneous equation probit models confirm that output losses following the crisis are persistent and conditional on the balance sheet indicator, that is, the ratio of the stock of gross external liabilities to assets. Measures of contingent liabilities, capital flight, and financial depth perform well as crisis predictors, and the marginal effects on the probability of a crisis are of the expected sign. The panel data set covers the time period 1973 through 2003 for 90 countries. "--World Bank web site